Features of application of immersive technologies of virtual and augmented reality in higher education - Anna Alexandrovna Paskova (Вестник Майкопского государственного технологического университета, 2023)
Augmented reality (AR) and virtual reality (VR) are immersive technologies that allow users to get acquainted with digital content both in physical and virtual space, expanding the possibilities of the educational environment.The relevance of the research is due to the growing introduction of virtual and augmented reality technologies in the educational environment.The research problem: what are the mechanisms for using immersive technologies of augmented and virtual reality in the field of innovative development of educational services in higher education?The aim of the research is to study the features of the application of immersive learning programs using AR/VR technologies in higher education.The methodological basis of the study is the analysis of Internet resources and literary sources, the study and generalization of pedagogical experience, synthesis.The results of the research are: the main advantages of using AR and VR technologies have been considered, possible options for introducing immersive educational technologies into the educational process proposed, the problems of their integration into the educational process of higher educational institutions and ways to overcome these problems identified.Key conclusions: AR/VR technologies are a promising addition to the educational space due to their immersive nature; in higher education, the use of immersive technologies can increase student engagement in the learning process, help students understand abstract concepts, allow for more personalized learning approaches, and improve learning analytics; when introducing AR / VR into the educational process. It is necessary to determine the goals and desired learning outcomes, choose a technology for work, organize a safe learning environment, plan the course structure. The main problems in the implementation of AR / VR are the high cost of technology and development, the need for regular software and hardware updates, health and safety risks for users, and technological problems.